2017
DOI: 10.1016/j.wocn.2017.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Focus marking in Dutch by heritage speakers of Turkish and Dutch L1 speakers

Abstract: Studies on heritage speakers generally reveal effects from the dominant L2 on the weaker L1, but it is less clear whether cross-linguistic transfer also occurs in the other direction: from the L1 to the dominant L2. This study explores whether the Dutch prosody of heritage speakers of Turkish in the Netherlands differs from that of L1 speakers of Dutch who do not speak Turkish, and whether observed differences could be attributed to an effect of Turkish. The experiment elicited semi-spontaneous sentences in br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Bullock (2009) reports the transfer of pitch accents from the dominant language, English, into the weak heritage language, French. In contrast, a study on utterances in broad focus (van Rijswijk et al 2017) finds differences in intonation and duration patterns, which are interpreted as evidence of transfer from the weak heritage language, Turkish into Dutch. Additionally, it has been reported that child heritage speakers (Queen 2001(Queen , 1996 show non-normative intonation patterns in both the heritage language, Turkish, as well as German.…”
Section: Introductionmentioning
confidence: 85%
“…Bullock (2009) reports the transfer of pitch accents from the dominant language, English, into the weak heritage language, French. In contrast, a study on utterances in broad focus (van Rijswijk et al 2017) finds differences in intonation and duration patterns, which are interpreted as evidence of transfer from the weak heritage language, Turkish into Dutch. Additionally, it has been reported that child heritage speakers (Queen 2001(Queen , 1996 show non-normative intonation patterns in both the heritage language, Turkish, as well as German.…”
Section: Introductionmentioning
confidence: 85%
“…As far as (2b) is concerned, note that there are not many studies on HSs focusing on the production of intonation patterns. Polinsky (2018) only cites works on the prosody of focus (e.g., Van Rijswijk et al (2017) on heritage Turkish in The Netherlands; Fenyvesi (2005) on heritage Hungarian in the US), which show that speakers tend to use the intonation patterns of their dominant language when producing foci. More in general, studies on the intonation of IHSs (Lloyd-Smith et al 2020) have shown that the majority of them do not sound "native-like", while a minority of them are perceived as native by homeland speakers: in Kupisch et al (2014), less than 33% of the HSs tested were rated as having a native intonation.…”
Section: Previous Studies On the Acquisition Of Anchementioning
confidence: 99%
“…Turkish Dutch children can thus be considered early sequential bilinguals who acquire Turkish as their L1 from birth and consistently start acquiring Dutch as their L2 in (pre) school. Others have coined Turkish-Dutch-speaking children heritage speakers (Kajouj & Kager, 2019;Van Rijswijk et al, 2017), as both Turkish and Dutch are present from birth and bilinguals often become dominant L2 speakers later in life (see also Meisel, 2004). Notably, for Turkish-Dutch-speaking bilingual children, it has been found that L1 Turkish is the strongest established language until well into primary school (Verhoeven, 2007) and continues to affect L2 processing well into childhood (Kajouj & Kager, 2019;Verhoeven, 2007) and even adulthood (Van Rijswijk et al, 2017).…”
Section: This Studymentioning
confidence: 99%
“…Others have coined Turkish-Dutch-speaking children heritage speakers (Kajouj & Kager, 2019;Van Rijswijk et al, 2017), as both Turkish and Dutch are present from birth and bilinguals often become dominant L2 speakers later in life (see also Meisel, 2004). Notably, for Turkish-Dutch-speaking bilingual children, it has been found that L1 Turkish is the strongest established language until well into primary school (Verhoeven, 2007) and continues to affect L2 processing well into childhood (Kajouj & Kager, 2019;Verhoeven, 2007) and even adulthood (Van Rijswijk et al, 2017). Therefore, in this article, we will refer to Turkish-Dutch-speaking children as sequential bilinguals.…”
Section: This Studymentioning
confidence: 99%